APPLICATION OF THE TIME TOKEN LEARNING MODEL IN AN EFFORT TO IMPROVE THE LEARNING ACTIVENESS OF CIVICS EDUCATION STUDENTS IN CLASS V OF SDN 79 LUBUKLINGGAU - Imel Permata Sari (Teaching and General Education Studies, 2025)
The lack of student participation and engagement in civics education has become a challenge in elementary classrooms, often due to monotonous and teacher-centred instructional methods. Increasing student activeness is essential for developing civic awareness and critical thinking skills at an early age. This research aims to describe the process of implementing the Time Token learning model in Civics learning and to describe the increase in student learning activity in Civics learning in Class V of SD Negeri 79 Lubuklinggau after implementing the Time Token model.This study used a classroom action research (CAR) approach, conducted in two cycles. Data collection techniques included tests, observation sheets, and documentation. The CAR process followed four stages: (1) planning, (2) implementing the action, (3) observing, and (4) reflecting. The research subjects were 17 fifth-grade students, consisting of 11 males and 6 females. Based on data analysis, the application of the Time Token model in online learning improved students’ activeness in civics education. This improvement was evidenced by an increase in the average post-test scores from 63.52 in Cycle 1 to 86.47 in Cycle 2. The findings demonstrate that the Time Token model effectively fosters student participation and engagement in Civics learning. It is recommended that educators adopt the Time Token strategy to promote active learning, particularly in subjects requiring discussion and student interaction. Future research may explore its application in other thematic subjects or different classroom settings.